American Institutional Review Boards: Safeguards or Censorship? - Hottenstein, Kristi N (The journal of research administration, 2018)
The United States is a world leader in biomedical clinical research. America's existing human subject research regulations structure affords sizable protections for the ethical treatment of research volunteers. Early initiatives such as the Belmont Report were specific to federally funded research. Over the past several decades guidelines such as the Belmont Report, along with more stringent policies, have been applied to non-federally funded research and research in the social sciences, and have branched out over areas, which many argue, they were not initially intended. Institutional review boards were codified to protect human subjects, an ethical and noble concern, but arguably these regulations were hastened both in response to a highly publicized research experiment and political considerations. This article explores the creation of the American IRB system through the lens of John Kingdom Multiple Streams Theory and examines critical viewpoints surrounding a longstanding inquisition over whether human subject research regulations are safeguards or censorship.